The The Effect of Audit Tenure, Auditor’s Reputation and Time Budget Pressure on Audit Quality - Danar Irianto Irianto (Pusat P2M Politeknik Negeri Batam, 2022)
This study aims to examine whether there is an effect of audit tenure, KAP reputation and time budget pressure on audit quality in companies listed on the IDX and the Issuer's website for the 2016-2020 period. This study has 3 independent variables, namely audit tenure, KAP reputation and time budget pressure and 1 dependent variable in the form of audit quality. The sampling method used is purposive sampling. This study uses a sample of manufacturing companies in the consumer goods industry sector. The sample of the number used is 55 of the 11 companies in the 5-year study. Secondary data used in this study with database collection techniques. Data analysis techniques using the coefficient of determination R2 and multiple linear regression analysis. The results showed that audit tenure, KAP reputation and time budget pressure had no significant effect partially or simultaneously on audit quality in manufacturing companies in the consumer goods industry sector.